Prison, subordination, inequality: again on a Marxist perspective - Melossi, Dario (Tracing the relationship between inequality, crime, and punishment, 2020)
This Chapter advances two claims which are related and sustain each other. The first is that in the contemporary “post-Fordist” world, the coupling of imprisonment and production persists in a relationship, if not between “the prison” and “the factory” - as Dario Melossi and Massimo Pavarini wrote 40 years ago - rather between “the prison” and “subordination”, because what all the multiple forms of “labor” and “non-labor” have in common - and have in common with the origins of protoindustrial capitalism - is subordination. The second is that the traditional reading of the “Rusche and Kirchheimer hypothesis” on the relationship between economic cycles and imprisonment depends on the specific conjuncture and class composition of the capitalist social formation to which it is applied. One thing is economic development in the period of Fordist mass industry and another in the globalized and fragmented labor market of neo-liberalism. Often imprisonment promotes phases of capitalist development rather than crises and recessions. Furthermore, subordination and inequality are strictly linked and feed on each other. Inequality promotes subordination, by putting the squeeze on those who are at the bottom of the social hierarchy; but subordination at the same time promotes inequality, by making sure that those who occupy those bottom positions, stay there. One strong link in the chain of subordination to inequality is penality, because penality reinforces inequality by reaffirming subordination. Data about long-run empirical relationships between imprisonment rates and inequality measures for the US and Italy are discussed.